`Wag mo `kong kausapin - Gacutan, Josef Dielle Perez 1995- (2018)
"Wag Mo 'Kong Kausapin is an animated film centered on Sixto, an elderly man who tries to repair his relationship with his estranged son. The film deals with the struggle of growing old and its psychological and physical repercussions, both embodied by the antagonizing black figure that only Sixto can see. The black figure invades Sixto's life, eventually culminating in the loss of Sixto's eyesight, and metaphorically, his loss against the regret and loneliness the black figure represented. It explores the concept of loneliness and regret whilst facing isolation in old age. Through the use of point-of-view shots and dream sequences, the filmmaker aims to better understand old age by exploring it through the most personal point of view: the elderly's."